Wajhu Dalalati al-Ayat al-Mutasyabihat fi Qisshotu Ibrahim ‘Alaihi as-Salam - Sujiat Zubaidi Saleh; Prima Rahmatika Ahmad (Universitas Darussalam Gontor, 2021)
This study is to investigate The Verses of Mutasyabihat,. It was one element of the al-Qur'ân which Contains various, miraculous and interesting aspects, the kind of this verse is mutashabihat lafziyyah. These verses have similar reduction but these have different meaning. Hence, every verse has its own purpose, different with each other such the story of the Prophet Ibrahim. It was because that there are repetition word that contain different meanings that can be understood by semantical analysis.This study revealed that the Mutashabihat verses in the story of the Prophet Ibrahim, have semantical aspects. The first deduction and addition in word Bal in the verse 70-73 of al-Syu’ara’ and deduction in the verse 52-53 of al-Anbiya’. The second is al-Ta’rif wa al-Tankir in the world al-Balad in the verse 126 of al-Baqarah and in the word balad in the verse 35 of Ibrahim. The third is al-Taqdim wa al-Ta’khir in the word al-Awwah and al-Halim in the verse 114 of al-Taubah and its opposite in the verse 75 of Hud. The forth is altering the words with another words, such as the word al-Halim in the verse 101 of al-Shoffat and the word al-‘Alim in the verse 26 of al-Dzuriyyat and in the verse 53 of al-Hijr.